The APB, Yield Indices, and Predictive Ability. - Hofstedt, Thomas R.; West, Richard R. (The Accounting Review, 1971)
Abstract The article discusses some of the theoretical problems of the cash yield (CY) and prime rate index (PR) of convertible bonds. Since most convertible bonds currently being issued are offered to investors at prices around par, differences between cash yields and yields to maturity tend to be rather insignificant. Accounting Principles Board (APB), attempted to justify its choice of the CY/PR index on the grounds first that it represents a practical, simple and readily calculable basis for making decisions, and, second, that it has a sound empirical basis founded on a relatively high degree of correlation between the prime rate and alternative yield indices. In essence, the Board recommended an eminently operational procedure having several obvious, serious theoretical flaws and questionable predictive ability. The APB's decision to compare cash yields on risky securities with an essentially riskless rate not only creates the relative bias but also tends to reduce absolutely the probability that any convertible issue will be classified as the equivalent of common stock.